Strong impact of management regimes on rhizome biomass across Central European temperate grasslands - Ottaviani, Gianluigi; Lubbe, Frederick Curtis; Lepš, Jan; Lisner, Aleš; Martínková, Jana; Mudrák, Ondřej; Klimešová, Jitka (Ecological applications, 2021)
Grassland ecosystems account for approximately 40% of terrestrial biomes globally. These communities are characterized by a large allocation to belowground biomass, often exceeding its aboveground counterpart. However, this biomass investment cannot be entirely attributed to the acquisitive function of roots. Grassland plants also allocate to non-acquisitive, stem-derived, belowground organs, such as rhizomes. These organs are responsible for the key plant functions of space occupancy, resprouting after damage, and seasonal rest. However, biomass investment to rhizomes has rarely been studied. Here we gathered community-level aboveground and rhizome biomass data for 52 temperate grasslands in Czech Republic (Central Europe), differing in management intensity. We found that rhizome biomass scaled linearly with aboveground biomass, and more intensive management disproportionally (negatively) affected rhizome biomass. This finding may have important implications for the persistence of temperate grassland plants and their provision of ecosystem services (e.g., soil carbon sequestration, soil stabilization) in relation to changing environments.
Keywords: disturbance; Evropa; Grassland; pastviny; Biomass; ekosystém; Soil; oddenek; mowing frequency; open ecosystems; Ecosystem; aboveground-rhizome biomass scaling; Rhizome; půda; Europe; biomasa; biomass allocation strategies